Sensorineural Hearing Loss as a First Presentation of Multiple Myeloma: A Successful Management with Therapeutic Plasma Exchange - Morteza Daraei; Ahmad Khajeh-Mehrizi; Behrooz Amirzargar; Fereshteh Ameli; Fahimeh Zeinalkhan (Case Reports in Clinical Practice)
Sudden sensorineural hearing loss (SSNHL) as the initial manifestation of multiple myeloma (MM) is rare. We present a 45-year-old woman with hyperviscosity syndrome (serum viscosity of 10.2 cP) from MM who presented with hearing disturbance that responded dramatically to plasma exchange with saline and intratympanic steroid treatment. Serum protein electrophoresis confirmed the presence of a monoclonal band, and bone marrow biopsy showed a hypercellular marrow with 90% plasma cells, which demonstrated lambda monoclonal restriction.